Treatment of Class II Division 2 Malocclusion Using the Forsus Fatigue Resistance Device and 5-Year Follow-Up - Ezgi Atik; Ilken Kocadereli (Case Reports in Dentistry)
This case report presents the treatment of a 14-year-and-8-month-old boy with Class II division 2 mandibular retrusion, severe deep bite, and concave profile. The Forsus fatigue resistance device (FRD) was effective in correcting both skeletal and dental parameters. At 5-year posttreatment follow-up, the teeth were well aligned and the occlusion was stable. FRD application with appropriate treatment time can result with prominent changes in the facial profile and dentition, and the outcomes can be maintained at the long-term follow-up periods.